2016
DOI: 10.4274/turkderm.75735
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of psoriasis in Trabzon

Abstract: Background and Design: Psoriasis is a chronic inflammatory skin disease affecting nearly 2% of the population. In Turkey, the only data about the prevalence of psoriasis from a population-based study is the data of the prevalence of 0.5% in a small district in a rural area. We aimed to provide the first large-scale data in Turkey by determining the prevalence of psoriasis in a large area, in the central and outlying districts of the province of Trabzon. Materials and Methods: A random sample of 7885 (4057 male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…However, this study was conducted in adolescents (age 12–20 years). Likewise, for adults, several studies found higher prevalence rates in men than in women,20,27,28,56–64 but other studies reported contrasting findings (Table S6; see Supporting Information) 14,21,22,29,65–71…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this study was conducted in adolescents (age 12–20 years). Likewise, for adults, several studies found higher prevalence rates in men than in women,20,27,28,56–64 but other studies reported contrasting findings (Table S6; see Supporting Information) 14,21,22,29,65–71…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, for adults, several studies found higher prevalence rates in men than in women, 20,27,28,[56][57][58][59][60][61][62][63][64] but other studies reported contrasting findings (Table S6; see Supporting Information). 14,21,22,29,[65][66][67][68][69][70][71] When examining variation in psoriasis prevalence between genders for all ages, the majority of the studies reported a higher prevalence rate in male than in female patients. 16,18,23,24,30,33,34,[36][37][38]40,51,[72][73][74][75][76][77][78][79][80][81] However, studies from Denmark, 31 Norway, 17,25,…”
Section: Variation In Incidence and Prevalence By Agementioning
confidence: 99%
See 1 more Smart Citation
“…Psoriasis is a chronic inflammatory skin disease that affects 2%-4% of the general population [21,22]. The prevalence of MS has been reported to be35% in the United States [21].…”
Section: Discussionmentioning
confidence: 99%
“…Despite various studies reporting that the incidence of psoriasis is higher either in females or males [ 33 ], there is a theoretical consensus on no gender discrimination in psoriasis incidence [ 6 ]. In a study on the incidence of psoriasis in Turkey, the prevalence of the disease is given as 1.2% in females and as 1.0% in males [ 69 ]. In another study, the female/male ratio in Turkish psoriasis patients has been reported as 200/129 [ 70 ].…”
Section: Discussionmentioning
confidence: 99%